Evaluation Of Growth And Development Of Stunting Childrens : A Case Control Study - Aurora, Wahyu Indah Dewi; Darmawan, Armaidi; Kusdiyah, Erny; Nuriyah, Nuriyah (FAKULTAS KEDOKTERAN DAN ILMU KESEHATAN UNIVERSITAS JAMBI, 2024)
ABSTRACT Background: Building the quality of human resources must go through a long process and is influenced by various factors. One of the most influencing factors is the intake of food with sufficient nutritional value for growth and development. The aim of this research is to comparison of growth and development of stunting childrens. Methods: This research was conducted in April – October 2023 with a case control research design. Population of this study are childrens with stunting in Jambi City, Indonesia . The research instrument used Developmental Pre-Screening Questionnaire (KPSP) and Denver Test. Variable evaluation of vision and hearing, evaluation of child's speech and language, physical examination, neurological examination, evaluation of other diseases and development. Results: The results obtained from this study were the majority were 25-36 months old 46.1%, with the largest gender being male 52.8%. No neurological or ear disorders were found in cases or controls. There was 1 eye disorder on physical examination, 3 disorders were found in cases and 1 disorder in controls. No significant relationship between variable. In the KPSP developmental examination, it was found that there were 44.4% developmental deviations in stunted children and have significant relationship between development and stunting. Conclusion: In terms of growth, stunted childrens do not experience any problems, but there are deviations in the development of stunted childrens.